Ragam Pemanfaatan Buku Teks Sebagai Media Pembelajaran Bahasa Inggris Di Kota Bitung Sulawesi Utara - Anis Komariah; Nur Halimah (Jurnal Ilmiah Iqra', 2022)
Various Utilization of Textbooks as Media for Learning English in Bitung City, North Sulawesi. This study aims to determine the criteria for determining textbooks as a media for learning English and the benefits, weaknesses, and advantages of textbooks. This research is qualitative and descriptive. The data collection techniques use in-depth interviews, observation, and documentation. The results of this study indicate that textbooks have a role as learning media in the teaching and learning process. 1) Criteria in selecting textbooks are: a) relevant to the curriculum, b) the material in textbooks is productive and receptive, c) The textbook material is based on the basic principles of learning foreign languages, d) Engaging content with media images in it, e) Have various types of evaluation that can measure learning achievement. 2) Using textbooks as media, learning resources, and learning evaluation tools. 3) Weaknesses and strengths of textbooks as a media for learning English a) unavailability of textbooks for each student, b) much material. Utilization Textbooks have advantages a) have a complete side, b) make it easier for teachers to deliver material, and visualization c) have varied questions